Dog's best friend? : rethinking canid-human relations - Sorenson, John, 1952-; Matsuoka, Atsuko Karin (McGill-Queen's University Press, 2019)
"In almost 40 per cent of households in North America, dogs are kept as companion animals. Dogs may be man's best friends, but what are humans to dogs? If these animals' loyalty and unconditional love have won our hearts, why do we so often view closely related wild canids, such as foxes, wolves, and coyotes, as pests, predatory killers, and demons? Re-examining the complexity and contradictions of human attitudes towards these animals, Dog's Best Friend? looks at how our relationships with canids have shaped and also been transformed by different political and economic contexts. Journeying from ancient Greek and Roman societies to Japan's Edo period to eighteenth-century England, essays explore how dogs are welcomed as family, consumed in Asian food markets, and used in Western laboratories. Contributors provide glimpses of the lives of street dogs and humans in Bali, India, Taiwan, and Turkey and illuminate historical and current interactions in Western societies. The book delves into the fantasies and fears that play out in stereotypes of coyotes and wolves, while also acknowledging that events such as the Wolf Howl in Canada's Algonquin Park indicate the emergence of new popular perspectives on canids. Questioning where canids belong, how they should be treated, and what rights they should have, Dog's Best Friend? reconsiders the concept of justice and whether it can be extended beyond the limit of the human species."--